Design of a Metamaterial Absorber - Sushree Subhasmita Patasani, Harish Chandra Mohanta (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
This paper describes the electric field-driven LC (ELC) resonator structure behaving as microwave absorbers at two different frequencies for the application of battlefield and airborne radar. The proposed ELC driven metamaterial structure is simulated and subsequently optimized using Ansoft HFSS which shows an absorption peak at 6.5 GHz and 10 GHz with peak absorbance of 99.1% and 99.9% respectively with S11 minima of -24.9 dB and -19 dB. The proposed structure also behaves as microwave absorber up to the angular incidence of 600.